Wedged Sensor in Distress? Lessons Learned from Troubleshooting Dampened Transmitted PA Waveforms of CardioMEMS Device - Robby Singh; Santo Scarfone; Marcel Zughaib (Case Reports in Cardiology)
Introduction. Cardiovascular disease is a leading cause of morbidity and mortality with heart failure constituting a large portion of this spectrum. Heart failure patients have 90-day readmission rates of nearly 41% associated with a high expense. Numerous strategies to reduce readmissions have been attempted with the CardioMEMS pulmonary artery pressure monitoring system as one of the more successful ones. As this device becomes used more frequently, it is important to recognize procedural complications. We present of a rare complication where a patient underwent successful device placement and was subsequently found to have dampened waveforms which were due to device migration. Case Report. A 79-year-old male underwent successful CardioMEMS placement due to recurrent heart failure hospitalizations. 6 months later, the transmitted waveforms appeared dampened, and repeat angiography revealed a device that had migrated. Rather than abandoning the device, it was recalibrated and continued to transmit data and helped manage the patient’s heart failure. Conclusion. CardioMEMS is a cost-effective tool to help reduce heart failure hospitalizations. Device migration is a rare complication and can lead to inaccurate data. However, as seen in this case, the device can be successfully recalibrated and can continue to be utilized to help reduce heart failure admissions.